2021
DOI: 10.51253/pafmj.v6i6.6462
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Rate of Chick Embryo Influenced by Nicotine and Antioxidant Green Tea (Camellia Sinensis)

Abstract: Objectives: To study the effects of Nicotine on the survival rate of chick embryo and to evaluate the preventive role by the antioxidant green tea camellia sinensis. Study Design: Laboratory-based experimental study. Place and Duration of Study: Army Medical College, Rawalpindi, from Nov 2011 to Nov 2012. Methodology: A total of 75 Fayoumi fresh fertilized eggs were kept at Poultry Research Institute, Rawalpindi. Experimental solutions were injected to the eggs of four groups at forty-eight h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The genotoxic and cytotoxic potential of Areca nut and smokeless tobacco were described [24]. In the study conducted by Shan et al [19,25] to observe the survival of nicotine-administered chick embryos observed a 90% survival rate in the control group and in that exposed to green tea extract, a 20% survival rate in the group administered nicotine, and a survival rate of 50% in the chicks exposed to both nicotine and green tea extract. The low survival rate of chicks exposed to nicotine could be a result of the hypoxic conditions created by nicotine-induced oxidative stress [25].…”
Section: Lower Survival Ratementioning
confidence: 99%
“…The genotoxic and cytotoxic potential of Areca nut and smokeless tobacco were described [24]. In the study conducted by Shan et al [19,25] to observe the survival of nicotine-administered chick embryos observed a 90% survival rate in the control group and in that exposed to green tea extract, a 20% survival rate in the group administered nicotine, and a survival rate of 50% in the chicks exposed to both nicotine and green tea extract. The low survival rate of chicks exposed to nicotine could be a result of the hypoxic conditions created by nicotine-induced oxidative stress [25].…”
Section: Lower Survival Ratementioning
confidence: 99%